Exercise-based rehabilitation in and with nature: a scoping review mapping available interventions - Henriette Busk; Jonas Ahler; Alessio Bricca; Pætur Mikal Holm; Dorthe Varning Poulsen; Søren T. Skou; Lars Hermann Tang (Annals of Medicine, 2023)
AbstractIntroduction Exercise is an effective component in rehabilitation of a range of chronic conditions. There is a growing interest in the use of exercise-based nature interacted rehabilitation (EBNIR), but an overview of current evidence is missing. The objective of this scoping review was to map existing exercise-based rehabilitation interventions conducted with incidental or intentional nature interaction focusing on its populations, types of outcomes, and theoretical rationale for people with physical and mental disabilities.Methods This scoping review identified peer-reviewed publications, registered upcoming trials and grey literature. To map all available knowledge, a comprehensive search of selected databases (MEDLINE; EMBASE; CINAHL; Cochrane; Web of Science; Pedro) from inception to October 2022. Data were synthesized in a thematic presentation guided by TIDieR, supplemented by a checklist developed for this study accounting nature incidental or intentional interaction.Results Twelve studies including 856 participants met the inclusion criteria. Eleven were completed trials and one was registered in clinicaltrials.gov to be run in 2023. A total of 856 patients were enrolled in the 12 studies (range 18–262, median 50). The included studies had great variation. The incidental or intentional interacted exercise-based interventions consisted of outdoor walks, neck exercises and surfing interventions in patients with physical or mental health conditions.Conclusions This scoping review presents an overview of limited and diverse evidence within the field of EBNIR, in patients with physical or mental health conditions. Our review provides an overview that will be helpful in the design of future EBNIR trials.